Contract Design for Rice Flour Supply Chain: Shipment Planning, Routing, Scheduling, and Invoicing - Juarsa, Rahmadini Payla; Kurnia, Eka; Aulia, Zesma; Djatna, Taufik (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2024)
The lack of proper planning and scheduling in the shipping process within the rice flour supply chain has resulted in various challenges, including missed products for consumers. This issue is particularly concerning due to the delicate nature of rice flour, which has a limited shelf life. Implementing a contract-based supply chain information system has proven to be beneficial in improving transparency and facilitating clearer information on product specifications to customers. The contract played an essential role because of the ability to adjust the description of a specific goal, enabling each supplier to customize the contract according to their needs. This customization includes specifying the duration of the product delivery process and the timeline for when consumers can expect to receive the product, thereby ensuring clarity and mutual understanding between all parties involved. Therefore, this research aimed to design business processes within the rice flour supply caused by using a contract, with a focus on minimizing distance and delays in routing and scheduling. Furthermore, it integrates the results of scheduling and routing with a contract in the form of invoices. The saving matrix method was used to calculate efficient shipping routes for distribution activities, resulting in a refined contract design tailored for rice flour transactions. The stakeholders included were the shipper manager, marketing department, and customers. By applying the saving matrix, this research effectively planned shipment scheduling and routing, optimizing the entire logistic process in the industry, and a prototype invoice design was developed for rice flour customers.